Construction of A Thermoelectric Coolbox System With Ice Pack Modification for Mango Storage Based on The Internet of Things - Fauzan Amri; Ardiansyah Rahma Putra; Moh. Abdul Gofur; Doli Bonardo (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
This study aims to design a thermoelectric system for a coolbox utilizing additional ice pack components for mango storage by leveraging a TEC1-12706 Peltier element based on IoT technology. Thermoelectric is an energy conversion technology that directly converts thermal energy into electrical energy and vice versa through thermoelectric materials. The system operates based on the Peltier effect, which generates a temperature difference between two sides of the material when an electric current is applied. Based on the test results, the developed thermoelectric system achieved a cabin temperature of up to 12.6 ºC within 60 minutes, according to the ideal storage temperature requirements for mangoes (12–15 ºC). The addition of an ice pack plays a significant role in accelerating the temperature reduction inside the cabin. The cold sink and heatsink components function effectively in absorbing and releasing heat to the environment. This system achieved a COP of 0.60 with an efficiency of 60%. The thermoelectric system has also been successfully integrated with IoT technology through the Blynk application, enabling users to monitor temperature and humidity in real-time via an internet-connected smartphone, thereby facilitating the control of mango storage conditions.